Risk assessment and prophylaxis of venous thromboembolism in surgical inpatients: improving adherence to national guidelines. Issue 1 (27th August 2015) - Johnson, Oscar; Kumar, Shankar
Abstract: In Europe, venous thromboembolism (VTE) is the third most common cause of vascular death after myocardial infarction and stroke. It is especially common during and after hospitalisation for surgery and acute medical illness though many other risk factors have now been identified. VTE is often preventable with judicious use of preventative measures in the form of thromboprophylaxis and mechanical antiembolism stockings. In 2014, a study was undertaken across all surgical wards at a teaching hospital in London to assess compliance to national guidelines for VTE risk assessment and subsequent institution of protective measures. The initial results demonstrated that performance could be improved in terms of meeting the national target of assessing 95% of surgical inpatients for risk of VTE at admission, prescribing anti-embolism stockings, ensuring that they are correctly worn, and reassessing patients 24 hours later. Utilising a multidisciplinary team approach, simple interventions were put in place such as e-mail reminders, posters, and senior input during ward rounds. Three subsequent measurements demonstrated that sustained improvement was achieved with the national guideline of 95% VTE risk assessment met. Improved performance was noted across all parameters considered, highlighting that simple intervention with all team members involved can improve patient safety and care.